A Two-Stage Cascade for Increased High-Value Product Accumulation in Chlamydomonas asymmetrica - Hahm, Joachim; Jung, Sun Hwa; Kandaswamy, Saikrishnan; Talwar, Prakhar; Verma, Nikita; Vivekanand, Vivekanand; Lindenberger, Christoph (Fermentation, 2024)
Cascade systems are used in the large-scale production of astaxanthin, facilitating a successful value-added process despite high accumulating costs. However, their application to other high-value products (HVPs), like lutein, β-carotene, chlorophylls, and fatty acids, remains unexplored. This study investigates Chlamydomonas asymmetica in chemostatic cultures, focusing on the impact of light and dilution rate. A two-stage cascade system is designed, combining high-light growth with low-light pigment accumulation. The results show potential for productivity improvement. Notably, the spacetime yield (STY) of Chlorophyll a increased by 20.96%, reaching 2.73 g·L−1·d−1 at the lowest dilution rate. Lutein maintains a consistent concentration of 22.34 mg·g−1, while β-carotene achieves a maximum STY of 3.60 mg·L·d−1. A cascade modification with a hollow fiber membrane significantly enhances HVP concentrations—Chlorophyll b, Lutein, Chlorophyll a, β-carotene, EPS, and GLA increase 27.23%, 38.95%, 31.88%, 86.19%, 128.7%, and 57.71%, respectively. STY improvements for these HVPs range from 1.78% to 82.96%. This study offers insights into C. asymmetica’s response and proposes a cascade modification for enhanced HVP production and downstream processing efficiency.
CRIS-Team Scopus Importer:2024-02-02
Keywords: C. asymmetrica; cascade; chemostat; chlorophyll a and b; exopolysaccharides (EPS); gamma linoletic acid (GLA); lutein; β-carotene